POLEMIK PENGISIAN KOLOM AGAMA DI KTP BAGI PENGANUT ALIRAN KEPERCAYAAN (Studi Pada Media Cetak, On-Line, dan Media Sosial Bulan November 2014) Polemics of Filling Out Column on Identity Card For Faith Followers (A Study of Print, On-Line, and Social Media in November 2014) - Mustolehudin Mustolehudin; Siti Muawanah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2017)
After the formation of “Kabinet Kerja” (Working Cabinet) during the reign of President Joko Widodo, Minister of Home Affairs, Tjahjo Kumolo expressed the idea of emptying the religious column on Identity Card (KTP) for faith followers (penganut kepercayaan). The idea has been getting a fairly diverse response from various circles either pros or cons. This study seeks to deeply explore that issue by using the ‘Critical Discourse Analysis’ method. It was conducted on print, on-line, and social media published in November 2014. The research findings show that first, the media attention, Republika as an Islamic-based daily newspaper is fairly high in responding to the issue (47%), Kompas 29%, Suara Merdeka 15%, social media (facebook) 7%, and Jawa Pos 2%. This data shows that Jawa Pos considers ‘Isu KTP’ (ID Card Issue)’ is not interesting. Second, the audience attitudes show that 61% rejected the removal of religious column (cons) then 17% supported (pros), and 22% (unclear). After a very long process, approximately 3 years, the faith believer (penganut kepercayaan) in Indonesia is recognized by the state by the decision of the Constitutional Court (Mahkamah Konstitusi) on November 7, 2017. The religious column on ID Card for faith believers (penganut kepercayaan) can be filled with “Penghayat Kepercayaan”.